The role of furin cleavage site in SARS-CoV-2 spike protein-mediated membrane fusion in the presence or absence of trypsin (2020)
Dear Editor, The rapid spread of SARS-CoV-2 (also known as 2019-nCoV and HCoV-191), a novel lineage B betacoronavirus (βCoV), has caused a global pandemic of coronavirus disease (COVID-19). It has been speculated that RRAR, a unique furin-like cleavage site (FCS) in the spike protein (S), which is absent in other lineage B βCoVs, such as SARS-CoV, is responsible for its high infectivity and transmissibility.2